New directions in assessing historical thinking - Ercikan, Kadriye; Seixas, Peter C. 1947- (New York Routledge/Taylor & Francis Group, 2015)
"Even as more school districts adopt history curricula that specify historical thinking as a goal, valid assessments of historical thinking remain elusive, and exams continue to focus on measures of factual knowledge or generic reading and writing skills. This edited collection addresses the new landscape of history learning and explores assessments of complex thinking in history. Topics covered include the design of formative and summative assessments for classroom purposes, methods of validating assessments of complex thinking, and assessing content versus procedural knowledge. With contributions from international experts from the fields of history education, digital humanities, and assessment and measurement, Assessment of Historical Thinking is a critical, research-oriented resource aimed at remedying the disjunction between the history classroom and the history test"--Provided by publisher.
Part I -- Historical consciousness in Germany : concept, implementation, assessment / Carlos Kèolbl & Lisa Konrad -- The difficulty of assessing disciplinary historical reading / Abby Reisman -- Heritage as a resource for enhancing and assessing historical thinking : reflections from the Netherlands / Carla van Boxtel, Maria Grever & Stephan Klein -- Relating historical consciousness to historical thinking through assessment / Catherine Duquette -- Commentary 1: Into the swampy lowlands of important problems / Robert B. Bain -- Part 2 -- Assessing for learning in the history classroom / Bruce VanSledright -- Historical thinking, competencies and their measurement : challenges and approaches / Andreas Kèorber & Johannes Meyer-Hamme -- A design process for assessing historical thinking : the case of a one-hour test / Peter Seixas, Lindsay Gibson & Kadriye Ercikan -- Material-based and open-ended writing tasks for assessing narrative competence among students / Monika Waldis, Jan Hodel, Holger Thèunemann, Meik Zèulsdorf-Kersting, & Beatrice Ziegler -- Commentary 2: Historical thinking : in search of conceptual and practical guidance for the design and use of assessments of student competence / Josh Radinsky, Susan R. Goldman, James W. Pellegrino -- Part 3 -- A large-scale assessment of historical knowledge and reasoning : NAEP U.S. history / Stephen Lazer -- Assessing historical thinking in the redesigned advanced placement United States history course and exam / Lawrence G. Charap -- Historical consciousness and historical thinking reflected in large-scale assessment in Sweden / Per Eliasson, Fredrik Alvâen, Cecilia Axelsson Yngvâeus, & David Rosenlund -- Commentary 3: Assessment of historical thinking in practice / Susan M. Brookhart -- Part 4 -- The importance of construct validity evidence in history assessment : what is often overlooked or misunderstood? / Pamela Kaliski, Kara Smith, & Kristen Huff -- Cognitive validity evidence for validating assessments of historical thinking / Kadriye Ercikan, Peter Seixas, Juliette Lyons-Thomas, & Lindsay Gibson -- Measuring up? : multiple-choice questions / Gabriel A. Reich -- History assessments of thinking : an investigation of cognitive validity / Mark Smith & Joel Breakstone -- Commentary 4: The validity of historical thinking assessments : a commentary / Denis Shemilt.
Includes bibliographical references and index.
Keywords: History -- Study and teaching; Critical thinking; Reflective learning; Learning -- Philosophy; Educational evaluation; Educational tests and measurements